SOCIAL STRUCTURE IN LITERATURE: A STUDY OF THE FINANCIER AND THE DEATH OF THE USURER - Mardanova Mohira Davron qizi (Modern American Journals, 2025)
This article examines the representation of social structure in Theodore Dreiser’s The Financier and Sadriddin Aini’s the Death of the Usurer. Despite emerging from different historical and cultural contexts, both works depict societies characterized by economic inequality, hierarchical power relations, and moral ambiguity.Through comparative analysis, the study identifies how social environment shapes characters’ ambitions, decisions, and ethical decline. Findings reveal that these authors use literary realism to expose the destructive influence of unequal social systems on human behavior and moral values.
Keywords: Social structure, inequality, realism, moral decline, Dreiser, Aini